Prague, the Victorious May of 1945 - S. V. Kudryashov (Vestnik MGIMO-Universiteta)
The article deals with complex and controversial issues related to the uprising and liberation of Prague in May 1945. Interpretation of the events became acute and caused lively discussions in connection with the demolition of the monument to Marshal I. V. Konev on April 3, 2020 by the order of the local municipality. The Czech Republic is also discussing the idea of «perpetuating the role of other liberators» of the capital – soldiers of the ROA division, which for two days (May 6-7) provided assistance to the rebels. Using new documents from the Central archive of the Ministry of defense of the Russian Federation, the author draws a conclusion about the limited influence of the Vlasov units. They, indeed, brought confusion to the German ranks, but early in the morning of May 8, they themselves left Prague on a rapid march. After that, fighting and negotiations between the rebels and the German command continued. The article emphasizes that the main goal of the Soviet military operation from 6 to 11 May 1945 was the defeat of the German Army Group Center. The liberation of Prague was only part of a powerful offensive by three Soviet fronts. Heavy battles for Prague did not happen, but the entry of Soviet tanks into the Czech capital and the subsequent jubilation of local residents became a symbol of the end of the war in Europe. The author concludes that the demolition of monuments to Soviet soldiers and commanders is a manifestation of internal political struggle in the countries where it occurs, and the Czech Republic is only one of these examples.